Would Perceived Organizational Spiritual Climate Matter If Spirituality Characteristics Influenced Physicians’ Intention to Quit? - Vem, Linus Jonathan; Ng, Imm Siew; Sambasivan, Murali (Review of Business Management, 2024)
Purpose – There has been a growing concern about physician turnover in sub-Saharan Africa. In this study, we explore the role of spirituality characteristics (SCs) and perceived organizational spiritual climate (POSC) on turnover intention (TI) among physicians in Nigeria, through the work-home interface (WHI). Theoretical framework – To understand the growing concern about physician turnover in the health sector, a multi-theoretical perspective is adopted. Workplace spirituality theory, role expansion and conflict theories interact to determine the extent to which SCs mitigate work-home resources (WHRs) and demands (WHDs) attenuate the intention to quit among physicians. Design/methodology/approach – Based on a two-wave questionnaire survey of 291 physicians practicing in Nigeria, an integrated framework was tested using Smart PLS 3.0. Findings –While SCs are insignificantly related to TI, they have a positive and significant relationship with WHRs and a negative and significant relationship with WHDs. In addition, WHRs have a negative relationship with TI, while WHDs have a positive relationship with TI. The moderating role of POSC between SCs and WHRs and WHDs was also established. Originality/value – This paper offers a first-hand assessment of the SCs construct as a formative variable. To the best of our knowledge, it is the first research effort to operationalize the construct and also provide a practical understanding of the negative side of spirituality through the moderating role of POSC.